Advocacy Of Civil Issues And Strengthening Legal Literacy For Religious Extension Workers Through Preventive And Conflict Resolutions Approach - Muhammad Romli Shofwan (NUSANTARA: Journal Of Law Studies, 2023)
This article discusses civil issue advocacy and efforts to strengthen legal literacy through preventive approaches and confllict resolution approaches. This research uses descriptive qualitative methods with phenomenological observative study techniques, where the author who is  actually one of the  Functional Islamic Extension Counselors is one of the elements actively involved at the time of the problem or event. The results of the analysis show that legal issues, especially civil ones, that occur in the community are very complex, ranging from disputes at the household level such as divorce cases, elopement, guardian adhal, inheritance to domestic violence cases. Likewise, cases whose effects involve more parties such as cases of disputes in determining the direction of Qibla, the legality of the status of waqf land, to cases of religious beliefs or splinter sects that often lead to horizontal conflicts. Using a preventive  approach and a confllict resolution approach, the author tries to elaborate and offer solutions to overcome these problems. The preventive approach is the most effective way, because with this approach it is like the saying  "it is better to prevent than to treat disease". So in essence, the preventive approach is a way to prevent conflict. At the same time, the resolution confllict approach is a method of solving problems where events or conflicts have occurred.